Provocation by eucapnic voluntary hyperpnoea to identify exercise induced bronchoconstriction. Issue 5 (1st October 2001) - Anderson, S D; Argyros, G J; Magnussen, H; Holzer, K
Abstract : The International Olympic Committee Medical Commission (IOC-MC) requires notification for use of a β2 agonist at the Winter Olympic Games in Salt Lake City. This notification will be required seven days before the event and must be accompanied by objective evidence that justifies the need to use one. The IOC-MC has expressed the viewpoint that, at present, eucapnic voluntary hyperpnoea (EVH) is the optimal laboratory challenge to confirm that an athlete has exercise induced bronchoconstriction (EIB). The EVH test recommended was specifically designed to identify EIB. EVH has been performed in thousands of subjects in both the laboratory and the field. The test requires the subject to hyperventilate dry air containing 5% carbon dioxide at room temperature for six minutes at a target ventilation of 30 times the subject's forced expiratory volume in one second (FEV1 ). The test conditions can be modified to simulate the conditions that give the athlete their symptoms with exercise. A reduction in FEV1 of 10% or more of the value before the test is considered positive.